Development of High-Pressure Extraction and Automatic Steam Distillation Methods for Aronia mitschurinii, Juvenile Ginger, and Holy Basil Plants - Sara Lahoff; Ezra E. Cable; Ryan Buzzetto-More; Victoria V. Volkis (Molecules)
Sample preparation is the most time-consuming part of phytochemical, agricultural chemical, and food science studies and is constantly being improved. This includes the development of modern extraction methods, such as high-pressure extraction and automatic steam distillation. These methods feature high reproducibility, low time consumption, and the ability to run several parallel samples. However, the ideal parameters for processing plant materials using these methods have not been fully explored. These parameters include those that produce the highest yield and those that produce yields comparable to less modern extraction techniques, which would allow for a comparison of data to a wide range of preexisting data obtained from plant materials in different growing locations and climates. As such, this study examined extracts produced by reflux extraction, high-pressure extraction, and traditional and automatic steam distillation for three plants: aronia, holy basil, and juvenile ginger. High-pressure extraction methods were developed to produce extracts similar to those produced by reflux extraction, while automatic distillation methods were developed to produce high essential oil yields. The automatic steam distillation yields were 55.81 ± 1.97 mg/g of holy basil, 61.52 ± 0.61 mg/g of ginger, and 45.79 ± 1.38 mg/g of aronia. The high-pressure extraction yields were 11.09 ± 1.46 mg GAE/g of holy basil, 154.50 ± 17.10 mg of anthocyanins/mL of aronia, 6.60 ± 0.55 mg GAE/g of ginger, and 3.27 ± 0.25 mg GAE/g of ginger. These were compared to reflux yields of 32.71 ± 5.22 mg GAE/g of holy basil, 253.00 ± 39.56 mg of anthocyanin/mL of aronia, and 3.34 ± 2.07 mg GAE/g of ginger.